2019
DOI: 10.1021/acs.joc.9b02816
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Catalyzed N-Alkylation of Arylamines and Arylamides with Benzylic Alcohols

Abstract: A sustainable boron-based catalytic approach for chemoselective N-alkylation of primary and secondary aromatic amines and amides with primary, secondary, and tertiary benzylic alcohols has been presented. The metal-free protocol operates at low catalyst loading, tolerates several functional groups, and generates H2O as the sole byproduct. Preliminary mechanistic studies were performed to demonstrate the crucial role of boron catalyst for the activation of the intermediate dibenzyl ether and to identify the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 89 publications
2
11
0
Order By: Relevance
“…S110, ESI ‡) rather than the generation of carbocations or ethers as reported for other metal-free N-alkylation mechanisms. 63,64 Such an observation indicates that the borrowing hydrogen mechanism is operative. Furthermore, to understand the role of KO t Bu, we have treated benzyl alcohol, 2a, with 1 equivalent N-benzylideneaniline, 5a, along with 10 mol% (N,O)-PLY and only 20 mol% KO t Bu resulting in 88% N-benzylaniline, 3a, aer isolation (Scheme 3a).…”
Section: Resultsmentioning
confidence: 92%
“…S110, ESI ‡) rather than the generation of carbocations or ethers as reported for other metal-free N-alkylation mechanisms. 63,64 Such an observation indicates that the borrowing hydrogen mechanism is operative. Furthermore, to understand the role of KO t Bu, we have treated benzyl alcohol, 2a, with 1 equivalent N-benzylideneaniline, 5a, along with 10 mol% (N,O)-PLY and only 20 mol% KO t Bu resulting in 88% N-benzylaniline, 3a, aer isolation (Scheme 3a).…”
Section: Resultsmentioning
confidence: 92%
“…In 2019, Chan and co‐workers showed that electron‐rich primary anilines undergo selective N ‐alkylation in nitromethane with a range of secondary and tertiary benzylic alcohols catalysed by BCF 4 (10 mol %) [9] . Subsequently, Maji disclosed the BCF 4 (1 mol %) promoted dehydrative alkylation of secondary anilines with a range of electron‐rich primary, secondary or tertiary benzylic alcohols [69] . The method was also applicable to the monoalkylation of primary sulfonamides.…”
Section: Dehydrative Alkylation Of Heteroatomsmentioning
confidence: 99%
“…[9] Subsequently,M aji disclosed the BCF 4 (1 mol %) promoted dehydrative alkylation of secondary anilines with ar ange of electron-rich primary,s econdary or tertiary benzylic alcohols. [69] The method was also applicable to the monoalkylation of primary sulfonamides.…”
Section: Dehydrative Cànb Ond Formationmentioning
confidence: 99%
“…Low reaction selectivity is the main cause . Typically, once alkylation of primary amine occurs, the resulting secondary amine with stronger alkalinity will compete with the primary amine, resulting in the formation of a tertiary amine . In severe cases, quaternary ammonium compounds will be obtained .…”
Section: Introductionmentioning
confidence: 99%